METHODOLOGICAL APPROACH TO TYPIZATION OF INFORMATION AND LOGISTICS SYSTEM ON THE BASIS OF OMNICHANALITY - KOLOSOK, Valeriia; PEDORENKO, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article introduces a detailed methodological approach to the typization of information and logistics systems (ILS) in business entities, grounded in the principles of omnichannel integration. In the face of digital transformation, increasing market volatility, and rising customer expectations, companies must optimize their logistics infrastructure while ensuring seamless service delivery across all channels. The authors propose a typization model that identifies three types of ILS—basic, adaptive, and fully omnichannel—based on six critical evaluation criteria: diversity and integration of communication channels, automation level, routing flexibility, processing speed, and the degree of personalization. This classification enables businesses to assess their current system’s maturity and identify potential areas for strategic enhancement. The paper highlights the importance of integrating marketing analytics with logistics operations to improve responsiveness, operational efficiency, and customer loyalty. It also emphasizes the need for real-time data synchronization and dynamic adaptability in supply chain processes. The developed methodology includes a step-by-step expert evaluation procedure with a quantitative scoring system to determine the ILS type and recommend directions for further development. As a result, the model serves as a practical, scalable management tool for digital enterprises striving to remain competitive in a rapidly evolving market environment. Through systematic assessment and guided transformation, organizations can achieve sustainable performance improvements, build stronger customer relationships, and enhance their market positioning within the omnichannel business landscape. Additionally, the proposed approach facilitates innovation-driven restructuring of logistics processes, aligning them with strategic goals, customer-centric policies, and modern technological capabilities, ensuring a higher level of integration, continuity, and adaptability in operations.